Risk and financial catastrophe - Banks, Erik. (New York : Palgrave MacMillan, 2009)
'The risk process commonly used in the corporate world to deal with risks may be suitable for non-catastrophic events, but not for extreme events. By analyzing a series of past disasters and the relevant'lessons learned', this books proposes a series of prescriptive measures to cope with future disasters'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Financial risk management; Emergency management; Risk management